SEJARAH ALIRAN KEPERCAYAAN MALIM DI KABUPATEN TOBA SAMOSIR 1907-1956 - Pesta P manurung; Bedriati Ibrahim; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The formulation of the problem in this research is the history of Malim tradition reliance in Toba samosir regency at 1907 up to 1956.The aims of this research is to research the Malim reliance concept, to research the history of Malim reliance before the colonial arrival which brought a new religion, to research the Malim reliance expansion under the leadership of the Nasiak bagi king(1907-1914), King Mulia naipospos(1907-1956),King Unkap Naipospos(1956-1981),and King Marmangkok naipospos(1981-now).The kind of this research is qualitative and descriptive.Through this research has founded the result of years King Nasiak bagi existence by composed the holy book which is called laklak. This book containof advises,laws and rules that trust it was came from God and delivered to King Nasiak bagi. King Mulia became the first king of Malim reliance after this reliance officially reveals in Tobasa. He was directly point out by Sisingamangaraja as the king to maintain the wholness of Malim reliance during colonial.The first result of king Nasiak Bagi is built up the Malim whorship place which it called Bale Pasogit and stand in Tobasa regency. The next result is forming the organization in Malim Reliance. The next king is King Ungkap Naipospos and his creation is success to built up a classified school for the Malim followers and made the country admiring them under culture and education ministry. The last king is Marnangkok king and his creation is renovate the Bale Pasogit center building in Laguboti. As the risen of education and Malim reliance follower and created a life book then received the civilian right through having Identity card.Keywords: History, Malim, Toba Samosir